MINDFULNESS OF PREGNANT WOMEN IN RELATION TO INVOLVEMENT IN TAPOVAN CENTRE OF CHILDREN’S RESEARCH UNIVERSITY - Prajapati, A. N.; Gajjar, Dharti N (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Pregnancy and childbirth are one of the most exciting and stressful experiences of a woman’s life. Pregnancy brings about physical, mental, and emotional changes, and, due to this, many changes are seen in women. During the nine months of pregnancy, women go through many physical, mental, and emotional ups and downs. Therefore, it is not necessary, but very necessary, to maintain the mindfulness of pregnant women in this state. Therefore, the purpose of the present research was to study the effect of family type and pregnancy sequence on the mindfulness of pregnant women in Tapovan Centre. In which 240 pregnant women were selected through a comprehensive demonstration method. The Mindful Attention Awareness Scale developed by Brown and Ryan (2003) was used for data collection. The Gujarati standardisation was done by Dr. A. N. Prajapati and Dharti N. Gajjar. The ’f-test’ has been used to statistically analyse the data. At the end of the present study, it was found that the pregnant women who participate in the Tapovan Centre have an increase in mindfulness compared to the non-participant pregnant women.